Discontinuous enrollment during college: Associations with substance use and mental health - Arria, Amelia M. (2013)
OBJECTIVE: To examine the prospective relationship of substance use and mental health problems with risk for discontinuous enrollment during college. METHODS: Participants were 1,145 college students interviewed annually at one large public university, beginning at college entry (year 1). Discontinuous enrollment was defined as a gap in enrollment of one or more semesters and operationalized as “early” (i.e., during the first two years) and “late” (i.e., during the second two years) versus “none” (i.e., continuously enrolled throughout college). Explanatory variables measured in year 1 were the Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), childhood conduct problems, cannabis use, number of illicit drugs used, and alcohol consumption. In years 3–4, participants reported lifetime history of clinically diagnosed ADD/ADHD, depression, and/or anxiety, including age at diagnosis. Multinomial logistic regression models were developed to evaluate the association between the independent variables and discontinuous enrollment, holding constant background characteristics. RESULTS: Higher BDI scores predicted early discontinuity but not late discontinuity, whereas cannabis and alcohol use predicted late discontinuity but not early discontinuity. Receiving a depression diagnosis during college was associated with both early and late discontinuity. None of the self-reported pre-college diagnoses were related to discontinuous enrollment once background characteristics were taken into account. CONCLUSION: Students experiencing depressive symptoms and/or seeking treatment for depression during college might be at risk for interruptions in their college enrollment. Cannabis use and heavy drinking appear to add to this risk. Students entering college with pre-existing psychiatric diagnoses are not necessarily at risk for enrollment interruptions.